Risk factors associated with delayed methotrexate clearance and increased toxicity in pediatric patients with osteosarcoma. Issue 4 (22nd December 2019) - Young, Elizabeth P.; Cheng, W. Susan; Bernhardt, Melanie B.; Wang, Lisa L.; Rainusso, Nino; Foster, Jennifer H.
Abstract: High‐dose methotrexate (HD‐MTX; 12 g/m 2 ) is part of standard therapy for pediatric osteosarcoma (OS). Risk factors associated with MTX toxicity in children with OS are not well defined. We investigated the association between peak MTX levels (four‐hour) and delayed MTX clearance or treatment toxicity. Information was retrieved from electronic medical records of 33 OS patients treated with HD‐MTX at Texas Children's Hospital from 2008 to 2015. We found that the four‐hour MTX level did not contribute to toxicity or delayed MTX clearance. We demonstrated that certain demographic characteristics are associated with delayed clearance and increased toxicity.